2020
DOI: 10.1007/s10750-019-04165-1
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the functional features of macrophyte communities and driving factors across a 70-year period

Abstract: Functional homogenisation occurs across many areas and organism groups, thereby seriously affecting biodiversity loss and ecosystem functioning. In this study, we examined how functional features of aquatic macrophytes have changed during a 70-year period at community and species levels in a boreal lake district. At the community level, we examined if aquatic macrophyte communities showed different spatial patterns in functional composition and functional richness in relation to main environmental drivers betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 69 publications
0
26
0
Order By: Relevance
“…Because of the high dispersal ability of aquatic plants by seed and vegetative propagules and owing to flexible reproductive systems (Eckert et al., 2016), spatial connectivity might enhance the landscape‐level ecological resilience (Allen et al., 2016). Also, due to high phenotypic plasticity, both morphological and ecological (Lacoul & Freedman, 2006), aquatic plant species can probably adapt to modest changes in the environment (Lindholm et al., 2020c). This issue combined with multiple interacting lake‐scale stressors, the complex community–environment relationships and stochastic processes might also explain why the environmental variables in our models cannot explain variation in the TBI between the 1940s and the 1970s.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the high dispersal ability of aquatic plants by seed and vegetative propagules and owing to flexible reproductive systems (Eckert et al., 2016), spatial connectivity might enhance the landscape‐level ecological resilience (Allen et al., 2016). Also, due to high phenotypic plasticity, both morphological and ecological (Lacoul & Freedman, 2006), aquatic plant species can probably adapt to modest changes in the environment (Lindholm et al., 2020c). This issue combined with multiple interacting lake‐scale stressors, the complex community–environment relationships and stochastic processes might also explain why the environmental variables in our models cannot explain variation in the TBI between the 1940s and the 1970s.…”
Section: Discussionmentioning
confidence: 99%
“…All studies reported consistent evidence for BH, with the exception of Lindholm et al (2020) who found little change in indicators of functional similarity of macrophytes among 28 boreal lakes between the 1950s (1947)(1948)(1949)(1950)(1951) and present day (2017). In the latter study, the authors highlighted that only modest environmental changes in boreal areas likely resulted in small community change over time.…”
mentioning
confidence: 81%
“…Past investigations of BH have largely focused on reconstructed species pools from published lists of native, extinct, and/or nonnative species, thus limiting comparisons to be made between some ''historical'' baseline and the present day (Rosenblad & Sax, 2017). In this special issue, Jia et al (2020) used data from a 50-year period; Brito et al 2020and Lindholm et al (2020) examined data over a 70-year period; Kirk et al (2020) leveraged historical data starting in the 1890's; and Peoples et al (2020) used an estimation of original fish fauna in North America before European colonization. One paper examined patterns of community composition before and after major dam construction , and other 5 papers used data from c. 10-20 years, coinciding with popularization of longterm ecological programs and standard ecological assessments.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As the water level drops, changes occur in the distribution and diversity of shoreline macrophytes. If a decline in the water level of a lake is continuous with slow recovery and refill time, native macrophytes may be replaced by invasive aquatic and semi terrestrial species [36,85,97]. Our study showed a decline in the surface water area and in macrophyte distribution.…”
Section: Anthropogenic Disturbances and Water Level Fluctuations Causmentioning
confidence: 56%